Copper removal and microbial community analysis in a single medium sediment microbial fuel cell. (December 2021) - Liu, Shu-Hui; Huang, Wun-Jie; Lin, Chi-Wen; Zhu, Ting-Jun
Abstract: In this study, we developed a single-medium, membraneless microbial fuel cell (SM-MFC) to examine the migration and types of Cu(II) migration in sediment and the difference in the microorganism community under various cathode conditions. To prevent O2 from competing with Cu(II) for electrons in the cathode and limiting the Cu(II) migration efficiency, we buried the cathode in sediment to facilitate Cu(II) migration. Modified stainless steel was used as a biocathode to increase electron migration in the MFC and enhance the electromigration of Cu(II). In the initial phase, voltages were applied to the MFC for microorganism acclimation, and the results revealed that the average voltage of the MFC reached 67.2 mV, which was 9.29 times higher than that of the MFC without voltage application. When the Cu(II) in the sediment is 172 mg/kg, after 100 days of operation, the MFC with a 10-cm electrode spacing exhibited the highest Cu(II) removal efficiency (57%) and voltage output (57.7 mV). The voltage output of the SM-MFC with a biocathode was 1.72 times higher than that of the cell with an abiotic cathode. The migrated Cu(II) formed Cu2 O and CuO at the cathode. The dominant bacteria phyla discovered at the cathode of the SM-MFC (i.e., Proteobacteria, Firmicutes, and Actinobacteria ) could degrade organic matter, generate electricity, and tolerate Cu(II). Graphical abstract: Unlabelled Image Highlights: Voltage application on an MFC reduced the acclimation period of microorganisms. Two types of Cu compounds discovered at the cathode indicate Cu(II) migration. A biocathode increased the performance of electron transfer. Dominant bacteria that can generate electricity and tolerate Cu(II) were observed.